DEVELOPMENT OF THE PENTUPLE BOTTOM LINE MODEL IN MODERATING THE EFFECT OF FINANCIAL LITERACY AND FINANCIAL INCLUSION ON MSME BUSINESS SUSTAINABILITY - Eris Juliansyah; Soekrisno Agoes; Nurmala Ahmar (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study employs a Systematic Literature Review (SLR) approach to explore and synthesize prior research regarding the impact of financial literacy and financial inclusion on the business aspirations of Micro, Small, and Medium Enterprises (MSMEs). It also examines the potential implementation of the Pentuple Bottom Line concept as a comprehensive moderation framework. The SLR process involved analyzing scholarly articles published between 2013 and 2024 across databases such as Scopus, Google Scholar, and ScienceDirect using relevant keywords. The findings indicate that both financial literacy and financial inclusion consistently exert a positive influence on MSME aspirations, particularly in the economic and social domains. Nonetheless, there is a noticeable gap in research that incorporates the environmental, social, and spiritual dimensions encapsulated in the Pentuple Bottom Line model. As a result, the adoption of this framework is suggested to reinforce MSME sustainability strategies. This study provides a conceptual contribution by introducing a novel perspective for research and practice in value-driven sustainable business development.